Helicobacter pylori: Pathogenic or mutualistic microorganism in Colombian populations - Guzmán, Kevin Andrés; Pazos, Alvaro (Universidad y Salud, 2023)
Introduction: The risk to develop gastric cancer varies between continents, countries and regions. Although there is a high prevalence of Helicobater pylori, its role as either pathogen or mutualistic bacteria defines the risk of gastric cancer in Colombian regions. Objective: To discuss the role of Helicobacter pylori in the risk of gastric cancer in Colombia. Materials and methods: A literature review based on searching LILACS, SciELO, and PubMed databases. Results: Helicobacter pylori role as either a pathogen or mutualistic microorganism associated with gastric cancer risk in Colombia can be explained by analyzing elements such as: human and Helicobacter pylori coevolution; cagA and vacA gene virulence; inflammatory (Th1) or anti-inflammatory (Th2) responses induced by Helicobacter pylori; human susceptibility to gastric cancer (IL1β, IL10); diet; and environmental factors. Conclusions: Even though Helicobacter pylori has a mutualistic role in populations at low gastric cancer risk (coastal regions), its role as a pathogen in populations at higher risk (Andean regions) justifies its eradication as a key strategy to mitigate the incidence of this cancer in Colombia.